Matematyka
jbialek
2017-06-25 09:18:45
zad 5 a 2 2/3-5 1/4+0,75 b 1 7/12+1 5/6-1/2:2/3 c -3,625-7 3/4+3 1/2:(-1 1/3) d (-2 2/3):(-1 1/5)-(5 1/18-6 1/9)
Odpowiedź
mafiozo0987
2017-06-25 15:26:08

a) 2 2/3-5 1/4+0,75=2 8/12-5 3/12+3/4= -2 7/12+9/12= -1 10/12=-1 5/6 b) 1 7/12+1 5/6-1/2:2/3=1 7/12+1 10/12-1/2*3/2=3 5/12-3/4=3 5/12-9/12= 2 8/12=2 2/3 c) -3,625-7 3/4+3 1/2:(-1 1/3)=-3,625-7,75+7/2:(-4/3)=-11,375+7/2*(-3/4)= -11,375+(-2,625)=-14 d) (-2 2/3):(-1 1/5)-(5 1/18-6 1/9)=(-8/3):(-6/5)-(5 1/18-6 2/18)= (-8/3)*(-5/6)-(-1 1/18)=40/18+19/18=59/18=3 5/18

aamorek1313
2017-06-25 15:27:23

zad 5. a) 2 i 2/3 - 5 i 1/4+0,75 = = 2 i 8/12 - 5 i 3/12 + 75/100 = = - 2 i 7/12 + 3/4= = - 2 i 7/12 + 9/12= = - 1 i 10/12= = - 1 i 5/6 b) 1 i 7/12+1 i 5/6-1/2:2/3 = = 1 i 7/12 + 1 i 10/12 - 1/2 * 3/2= = 2 i 17/12 - 3/4 = = 2 i 17/12 - 9/12 = = 2 i 8/12= = 2 i 2/3 c ) -3,625-7 i 3/4+3 i 1/2:(-1 i 1/3) = = - 3 i 625/1000 - 7 i 3/4 + 7/2 : (- 4/3) = = - 3 i 5/8 - 7 i 6/8 + 7/2 * (- 3/4) = = - 10 i 11/8 + (-21/8)= = - 11 i 3/8 - 2 i 5/8 = = - 13 i 8/8= = - 14 d) (-2 i 2/3):(-1 i 1/5)-(5 i 1/18-6 i 1/9) = = (-8/3) : (-6/5) - (5 i 1/18 - 6 i 2/18) = = (-8/3) * (-5/6) - (4 i 19/18 - 6 i 2/18) = = 40/18 - (-2 i 17/18) = = 2 i 4/18 + 2 i 17/18 = = 4 i 21/18 = = 5 i 3/18 = = 5 i 1/6

Dodaj swoją odpowiedź